Effect of Javanese Turmeric (Curcuma xanthorrhiza) Extract on Hepatitis Model of Alcohol-Induced Mice - Puteri, Agnes Ilene Suprapto; Sandhika, Willy; Hasanatuludhhiyah, Nurina (Jurnal Kedokteran Brawijaya, 2020)
Alcoholic hepatitis is a common cause of non-viral hepatitis. Javanese turmeric (Curcuma xanthorrhiza) contains xanthorrhizol and curcuminoid that have antioxidant and anti-inflammatory effects. The purpose of this research was to detect the effect of Curcuma xanthorrhiza in decreasing hydropic degeneration and lymphocytes in alcohol-induced mice. This experimental research used post-test only controlled design. Randomly, 35 mice were divided into five groups. Four groups were induced by alcohol 30% of 4ml/kgBW in 10 days, and one group was normal group (negative control). Three of the four alcohol-induced groups were given Curcuma xanthorrhiza extract at doses of 42, 84, and 168 mg/kgBW in 10 days, 1 hour after alcohol induction. Mice livers were taken for Hematoxylin Eosin (HE) staining.Â  Hydropic degeneration and lymphocytes in the liver lobules were examined under a microscope. The statistical analysis used in this research was the Kruskal-Wallis, the Mann-Whitney test, and the Independent Sample T Test. P-value is significant if <0.05. The result of this research were all doses of Javanese turmeric extract significantly reduced hydropic degeneration. Doses of 84 and 168 mg/kgBW also reduced inflammatory lymphocytes (p<0.05). The dose of 168 mg/kgBW reduced the lymphocyte inflammation maximally. There was no significant difference between increasing Javanese turmeric dose and decreasing hydropic degeneration and lymphocytes (p>0.05). This research shows that Javanese turmeric (Curcuma xanthorrhiza) can attenuate hepatitis by decreasing hydropic degeneration and lymphocytes in alcohol-induced liver.